Концептуальні засади підготовки майбутніх журналістів до професійно-творчої діяльності - Дяченко, Марія (Видавництво Львівської політехніки, 2012)
В статье освещены научные взгляды на процесс формирования творческой личности, сделана попытка раскрыть сущность журналистского профессионализма, определить педагогические условия для развития творческой личности будущего журналиста в процессе профессионального образования. The article deals with the scientific views on the process of formation of the creative personality. The author makes an attempt to reveal the essence of the journalistic professionalism and to determine the pedagogical conditions for the future journalists’ creative personality development in the process of professional education.
Концептуальные основы подготовки будущих журналистов к профессионально-творческой деятельности
Conceptual principles of future journalists’ training to professional and creative activity
Keywords: журналист; профессиональное образование; развитие; профессионализм; самореализация; творческая личность; творчество; journalist; professional education; development; professionalism; self-realization; creative personality; creativity